High‐Performance Photoinitiating Systems for Free Radical Photopolymerization. Application to Holographic Recording1. (21st August 2013) - Ibrahim, Ahmad; Stefano, Luciano Di; Tarzi, Olga; Tar, Haja; Ley, Christian; Allonas, Xavier
Abstract: The photoinitiating systems (PIS) usable in free radical photopolymerization are briefly reviewed. Apart conventional Type I and Type II photoinitiators, three‐component PIS exhibiting a photocyclic behavior are discussed. The mechanisms of photoreaction are presented, highlighting the role of a redox additive which reacts with the photoinitiator photoproduct. Recent applications in holography recording are described showing that the selection of a PIS plays a crucial role in this application. Abstract : To overcome the lack of reactivity of PIS for free radical photopolymerization under visible light, photocyclic initiating systems have been developed. In such systems not only the intrinsic problem of reactivity of the Type II system is circumvented, but also the dye is recovered after reaction. These systems are based on a dye as absorbing species, an electron or hydrogen donor as coinitiator and a redox additive which aims to react with the photoproduct formed from the dye. These systems can be used to improve the photosensitivity in holography recording.